"Quem não pode com a formiga não assanha o cajueiro”: necropoder, margens e interstícios da judicialização do conflito socioambiental na Comunidade do Cajueiro, em São Luís – MA - PEDRO, Viviane Vazzi (2017)
ABSTRACT In this thesis, I analyze the "political judicialization" of the confrontation in the case of socioenvironmental conflict that occurs in the Cajueiro Community, in São Luís, Maranhão, from the pretension, of a company that presents itself as WPR São Luís Gestão de Portos Ltda. of installing a port and logistics terminal for private use in the region. The ethnography of the case and the arenas of the dispute - official or otherwise - reveals interstices, margins and various meanings of justice, based on different forms of investigation and exercise of micropowers exercised by hybrid agents and institutions, which become part of the daily life of Residents, interfering in their lives, leading to evictions, creating internal norms and "truths" under "almost legal" or "almost official" masks, as well as mechanisms for control, surveillance, punishment and death policies on the spot. The construction of the thesis was done by the identification and analysis of the mechanisms of power, formal and non-formal mechanisms used by groups involved in the conflict and in interaction with the Community, and related to the processes of judicialization. I sought to understand what these devices were, how and by whom they were triggered, and their repercussions, in order to understand the character assumed by "political judicialization", the form of the "State in action" and its effects on conflict. Looking at the process of "political judicialization" of this conflict - beyond the judicial system - I realize that there is a large marginalized or interstitial-violent space in which a network of civil, corporate, hidden agents, "almost public and almost Private, "they act in concert, by means of power devices clothed with the legal appearance and other mechanisms of legitimacy that constitute a kind of local "extra, intra, trans, ultrastate" necropower (MBEMBE, 2011, 2012, 2015). In this case, this combination of powers and devices does not allow us to speak in a State, as we know it, but in an "indirect private government" (MBEMBE, 2011, 2012), through which locally, agents and institutions interested in the terminal Port authorities exercise powers of jurisdiction, sovereignty, coercion and violence to enact and exercise a policy of death and sacrifice for the rights and families of Cajueiro.